ANALISIS PERFORMANSI JARINGAN FRAME RELAY VIRTUAL PRIVATE NETWORK - Ningsih, Yuli Kurnia; Surjati, Indra; Faiq, Alfian Noor (Jurnal Teknik Elektro, 2005)
Frame relay, according to its name, is a technology that depends on frames thatâs beingrelayed in a data transmission. This technology is a simplified form of packet switching,similar in principle to X.25, in which synchronous frames of data are routed to differentdestinations depending on header information [Bates,2002:57]. A regular analysis on networkperformance and quality must be taken to guarantee certain service level. This task is soimportant as frame relay usually carries data on high speed data communication backbone.The performance analysis from the Frame Relay network will be discussed at the providingcompany. Performance analysis is useful to know the quality of service from the Frame relaynetwork . To analyze the quality of service from the Frame relay network can be seen from themeasurement that can affect the network. There are three measures which can affect thenetwork significantly such as bus utilization, excess burst percentage and dropped packetpercentage. Those three are closely related and having significant impact on overall framerelayâs network quality. Based on the results from the networks analyzed shows that it hasenough processing power and bandwidth resources, eventhough nearly 30% of their networkpath is under specified service level guarantee. Even so, overall quality of frame relaynetwork meets the specified service level quality.Keywords: Frame Relay, Bus Utilization, Excess Burst Percentage, Dropped PacketPercentage